Performance test on composite beam with trapezoid web profile (TWP) steel section - 198532 Goh, Kee Keong (Skudai : Universiti Teknologi Malaysia, 2002)
Thesis (Master of Civil Engineering (Structure)) - Universiti Teknologi Malaysia, 2002